SISTEM KEAMANAN JAIL BASH UNTUK MENGAMANKAN AKUN LEGAL DARI KEJAHATAN INTERNET MENGGUNAKAN THC-HYDRA - Cakra Aminuddin Hamka; Haruno Sajati; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2014)
Along with the development of current technology, making technology is very important in today's life. Security level digital data has become more vulnerable to exploitation, the problem arises when an information technology device was attacked by people who do not want to take a responsible and important data illegally, so the administrator must act quickly to secure important data. Making a data security technology on the internet is very important information. Limitations administrator underlying the creation of a system that is able to detect and defense systems against such attacks is automation, so that it can be applied to data security. The system is built to prevent attacks on computer networks with more specific on THC - Hydra. This system will analyze the number of errors in the log into the database, and if the error exceeds the tolerance rules are made by the administrator. If the error is more than 3 times in one minute, then with automation, the system will create a rule that can imprison users who do not have such access, and access to the prison in the illegal user can not perform such activities on legal access and access to activities conducted illegal user can be recorded on a file and jail.txt. So under any circumstances and not in supervising administrator, the security of other user data will be safe and can not be retrieved or viewed by a user of illegal access.